EXPLORING DIGITAL ETHNOGRAPHY APPLIED TO LANGUAGE LEARNING STUDY: A LITERATURE REVIEW - Febriyanti, Rina Husnaini; Lustyantie, Ninuk (IJLECR (International Journal of Language Education and Cultural Review), 2020)
Abstract The digital or virtual atmosphere in the education field today begins to spread which includes in the area of language learning. In line with that one, a research design is proposed in a similar context that is Digital Ethnography (DE). The research aims are to reveal and explore the detail of DE and how it is implemented in research. The method used in this study is qualitative, and the data is collected from 10 articles from reputable journals that discuss DE. The collected data were categorized based on the year, title, author, purpose, method result and discussion, and conclusion, afterward they were analyzed and presented descriptively. The findings of this study showed that DE can be applied in various topic particularly in language learning research. The implication of this study DE can be as one of the options as the research design related to language learning in a digital or virtual context.